Inland fisheries management in Cambodia : - Degen, Peter (The seventh Common Property Conference of the International Association for the study of Common Property, 1998)
The process of gradually deepening insight aslo allows for gradually improving the operationalization of research questions that provide a clearer picture of the essential for fisheries management.